The Level of Trust of the People of DKI Jakarta in the Policy Made by DKI Jakarta Provincial Government in Dealing with the Covid19 Pandemic - Irfan Alvianto; Renny Nurhasana; Ummi Salamah (Lekesan: Interdisciplinary Journal of Asia Pacific Arts, 2021)
The Covid-19 pandemic which has affected the lives of all people around the world has also affected Indonesia's capital city, DKI Jakarta. The DKI Jakarta Provincial Government must be able to regulate all of its people so that they can live according to health protocols and reduce the very fast spread of Covid-19 infections. In this case, information concerning health protocol becomes very important so that it can be applied by all communities. The spread of information carried out in social media belonging to the DKI Jakarta Provincial Government must be done well so that the public can understand and implement the regulations or policies that has been made. This research takes the case of public trust in the Provincial Government of DKI Jakarta in tackling Covid-19 by analyzing 3 variables, Satisfaction, Transparency and Interactivity. Quantitative methods are carried out by distributing questionnaires to answer research questions. An important finding in this study is that interactivity is the dominant variable affecting public trust in the Provincial Government of DKI Jakarta.